Green Maritime Corridor Development: Infrastructure Performance andEco-Efficient Design Strategies toward IMO 2050 Decarbonization - Ramadhan Hasri Harahap; M. Anang Jatmiko; A. Nurfajri Irwan; Ikhwanuddin; Giovanni Battista Puteri (Momentum International Journal of Civil Engineering (MIJCE), 2026)
Maritime transport's contribution of approximately 3% to global CO2 emissions necessitates urgent infrastructure transformation to achieve the International Maritime Organization's 2050 net-zero targets. This research develops a comprehensive Green Maritime Corridor framework integrating coastal infrastructure planning, alternative fuel bunkering networks, and emission control zones through evidence-based spatial optimization methodologies. Employing qualitative analysis incorporating perspectives from maritime engineers, environmental specialists, and logistics operators, this study identifies critical infrastructure requirements, technological readiness levels, and implementation barriers constraining decarbonization progress. The framework synthesizes transportation engineering principles with environmental sustainability imperatives, demonstrating how strategic corridor development can simultaneously reduce maritime emissions while enhancing operational efficiency and economic competitiveness. Findings reveal significant gaps in current infrastructure planning approaches, particularly regarding alternative fuel supply chain coordination and regulatory harmonization mechanisms. The research contributes actionable implementation pathways for maritime stakeholders globally, offering evidence-based strategies for accelerating shipping decarbonization aligned with Paris Agreement commitments and SDG 13 (Climate Action), while maintaining maritime transport's essential role in global trade through technologically advanced, environmentally responsible infrastructure systems.